2019
DOI: 10.1002/prca.201800038
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ‐Based Quantitative Proteomics Approach Identifies Novel Diagnostic Biomarkers That Were Essential for Glutamine Metabolism and Redox Homeostasis for Gastric Cancer

Abstract: Purpose: To screen the novel biomarkers for gastric cancer and to determine the values of glutaminase 1 (GLS1) and gamma-glutamylcyclotransferase (GGCT) for detecting gastric cancer. Experimental design: A discovery group of four paired gastric cancer tissue samples are labeled with Isobaric tag for relative and absolute quantitation agents and identified with LC-ESI-MS/MS. A validation group of 168 gastric cancer samples and 30 healthy controls are used to validate the expression of GLS1 and GGCT. Results: Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…With iTRAQ, the protein expression levels can be compared simultaneously [16]. iTRAQ technology has been applied to muchresearch: To identify prognostic biomarkers for gastric cancer [17]; to reveal potential novel biomarkers for the early diagnosis of acute myocardial infarction within three hours [18]; to identified SAA and ACTB as potential biomarkers in patients with severe hand, foot, and mouth disease (HFMD) [19], to discover glioblastoma serum markers [20], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…With iTRAQ, the protein expression levels can be compared simultaneously [16]. iTRAQ technology has been applied to muchresearch: To identify prognostic biomarkers for gastric cancer [17]; to reveal potential novel biomarkers for the early diagnosis of acute myocardial infarction within three hours [18]; to identified SAA and ACTB as potential biomarkers in patients with severe hand, foot, and mouth disease (HFMD) [19], to discover glioblastoma serum markers [20], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al used targeted proteomics coupled with immunoaffinity enrichment to investigate epithelial ovarian cancer samples and found that the combined AUC for serum carbohydrate antigen 125 (CA125) and heat shock protein 27 was 0.88, which was significantly higher than that of CA125 alone [25]. Jiang et al performed iTRAQ labeling and LC-ESI-MS/MS to evaluate a discovery group of four GC samples and four adjacent healthy tissues [26], and found an AUC of 0.734 for GLS1 and GGCT co-expression, suggesting that the level of co-expression had high clinical value as a diagnostic biomarker for early GC.…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope labeling uses the mass increase caused by the mass tags with incorporated stable isotopes to quantify peptides at the MS1 full scan (precursor ion) level or peptide fragments at the MS2 (production ion) scan level. There are several strategies to label peptides or proteins with stable isotopes: chemical labeling such as Isobaric Tags for Relative and Absolute Quantitation (iTRAQ) [ 97 , 100 , 101 , 102 ] and Tandem Mass Tags (TMT) [ 103 , 104 , 105 , 106 ], and metabolic labeling strategies such as Stable Isotope Labeling by Amino acids in Cell culture (SILAC) [ 107 , 108 , 109 , 110 ]. Data independent acquisition (DIA) methods can also be used for quantitative studies ( Figure 1 ).…”
Section: Mass Spectrometry For Biomarker Developmentmentioning
confidence: 99%